Nurse manager practice environment in hospital context: scoping review - Ana Nascimento; Elvio Jesus; Beatriz Araújo (Millenium, 2025)
Introduction: Nurse managers play a key role in healthcare organizations, particularly in promoting favorable practice environments for nurses in clinical practice. However, the knowledge about their own practice environment is under-explored.